A case report of coronavirus disease‐2019‐induced acute asthma exacerbation in an obese patient. Issue 7 (7th June 2022) - Sasaki, Hisashi; Miyata, Jun; Kobayashi, Ai; Kawano, Shuichi; Kawana, Akihiko
Abstract: The coronavirus disease‐2019 (COVID‐19) has spread worldwide. Previous studies indicated a low prevalence of COVID‐19 induced acute exacerbations of asthma. We present a 39‐year‐old‐male obese asthmatic case who experienced acute asthma exacerbation during COVID‐19. On day 8 of infection, his cough and dyspnea worsened with hypoxia and wheezing. Laboratory test results revealed elevated interleukin‐6 (IL‐6) and total immunoglobulin E (IgE) levels without eosinophilia. Two months since the onset, hypoxia disappeared with decreased IL‐6 and IgE levels. Our case suggested that obesity and high serum IL‐6 and IgE levels may have contributed to atypical asthma exacerbation in COVID‐19. Abstract : The coronavirus disease‐2019 (COVID‐19), an emerging infectious disease caused by Severe Acute Respiratory Syndrome‐Coronavirus 2 (SARS‐CoV2), emerged in December 2019 and has spread worldwide. Old age, hypertension, diabetes, and smoking were identified risk factors for aggravation. Obesity also increases the severity and mortality of COVID‐19. However, the relationship between asthma and COVID‐19 infection remains unclear. We present a rare case of an obese asthmatic patient who experienced asthma exacerbation during COVID‐19 infection.